Karakteristik dan Pola Hidup dengan Kejadian Batu Ginjal di Poliklinik Urologi Rumah Sakit Pertamedika Ummi Rosnati Banda Aceh - Hardian, Muhammad; Desreza, Nanda; Masthura, Syarifah; Sufri, Sofyan (Poltekkes Kemenkes Aceh, 2024)
Background: Kidney stones are one of the 3 most common diseases in the field of urology after urinary tract infections and benign prostate enlargement. This disease usually occurs at the age of 60 – 69 years and occurs 3 – 4 times more in men than women. The procedures that are often performed are non-invasive. Purpose: Knowing the relationship between characteristics and lifestyle with the incidence of kidney stones. Methods: This research is a quantitative research with a cross sectional analytical research design. The sample for this study was 47 kidney stone patients at the Pertamedika Ummi Rosnati Hospital, Banda Aceh. Results: From the results of the Fisher Exact analysis, it was found that the relationship between characteristics and lifestyle with the incidence of kidney stones included age (p=0.003), occupation (0.046), activity status (0.007), diet (0.005) and elimination pattern (0.001). Meanwhile, education (0.560) had no relationship with the incidence of kidney stones. Conclusion: There is a relationship between age, occupation, activity status, diet and elimination patterns with the incidence of kidney stones. Meanwhile, education has no relationship with the incidence of kidney stones.